Is reduced freshwater flow in Tigris-Euphrates rivers driving fish recruitment changes in the Northwestern Arabian Gulf?. Issue 1 (April 2018) - Ben-Hasan, A.; Walters, C.; Christensen, V.; Al-Husaini, M.; Al-Foudari, H.
Abstract: Like fishing, natural regime shifts and human-induced environmental changes are often equally important factors in driving fish stock declines. In the Northwestern Arabian Gulf, many fish stocks are declining, raising questions about the reduction in the flow of Tigris-Euphrates rivers. Here we investigate the relationship between Tigris-Euphrates river flow and the estimated recruitment patterns from assessment models. We found a positive correlation between the estimated finfish recruitment trends and the flow of Tigris-Euphrates rivers. Additionally, the assessment model showed remarkably weak compensation ratio, likely indicating a reduction in the productivity of nursery area of two finfish stocks but not in that of the crustacean stock. Our investigation would be very critical in providing guidelines to the government agencies in the Northwestern Arabian Gulf as well as countries of Tigris-Euphrates basins: to consider the impacts associated with reductions in Tigris-Euphrates river flows on the ecosystem services of the region. Highlights: The impact of damming Tigris-Euphrates rivers on the fish stocks in the Northwestern Arabian Gulf has been investigated Positive correlation was found between fish recruitment trends and the flow of Tigris-Euphrates rivers Weak compensation ratio estimated for some fish stocks may indicate a reduction in the productivity of the nursery areas